Anodic electrogenerated chemiluminescence behavior and the choline biosensing application of blue emitting conjugated polymer dots. Issue 45 (16th May 2016) - Chen, Hongmei; Lu, Qiyi; Liao, Jiayao; Yuan, Ruo; Chen, Shihong
Abstract : The anodic electrochemiluminescence (ECL) behavior of poly(9, 9-dioctylfluorenyl-2, 7-diyl) (PFO) dots was studied and applied in oxidoreductase-based ECL biosensing using Chox as the model enzyme. Abstract : The anodic electrochemiluminescence (ECL) behavior of poly(9, 9-dioctylfluorenyl-2, 7-diyl) (PFO) dots was studied and applied in oxidoreductase-based ECL biosensing using Chox as the model enzyme.